Class size and class heterogeneity - Giacomo De Giorgi; Michele Pellizzari; William Gui Woolston (Institute for the Study of Labor (IZA), 2009)
We study how class size and composition affect the academic and labor market performances of college students, two crucial policy questions given the secular increase in college enrollment. We rely on the random assignment of students to teaching classes. Our results suggest that a one standard deviation increase in the class-size would result in a 0.1 standard deviation deterioration of the average grade. Further, the effect is heterogenous as female and higher income students seem almost immune to the size of the class. Also, the effects on performance of class composition in terms of gender and ability appears to be inverse U-shaped. Finally, a reduction of 20 students (one standard deviation) in one's class size has a positive effect on monthly wages of about 80 Euros (115 USD) or 6% over the average.
Keywords: A22; I23; J30; 330; Class size; heterogeneity; experimental evidence; academic performance; wages; Bildungsniveau; Studierende; Bildungsertrag; Akademische Berufe; Studium; Klassengröße; Test; Italien